Neurofibromatosis Type 1 Associated with Vertebrobasilar Dolichoectasia and Pontine Ischemic Stroke. Issue 3 (18th September 2014) - Giannantoni, Nadia Mariagrazia; Broccolini, Aldobrando; Frisullo, Giovanni; Pilato, Fabio; Profice, Paolo; Morosetti, Roberta; Di Lella, Giuseppe; Zampino, Giuseppe; Marca, Giacomo Della
ABSTRACT Neurofibromatosis type 1 (NF1) is a heterogeneous, common, neurocutaneous disorder presenting different complications during a life span, including cerebrovascular dysplasia. To our knowledge this is the first reported case of NF1 associated with vertebrobasilar dolichoectasia and pontine ischemic stroke. We describe a 57‐year‐old man with NF1 who presented an acute onset right‐sided facial palsy and hemiplegia, dysarthria, and gait imbalance. Magnetic resonance imaging showed an acute left paramedian pontine infarct and a hypoplastic right vertebral artery. Brain Computed Tomography Angiography revealed the occurrence of vertebrobasilar dolichoectasia. Co‐occurrence of VBD and NF1 might not be merely casual and it may significantly heighten the mortality rate in this multisystem disorder. We suggest a possible role of VBD in the genesis of our patient's clinical‐radiological features and prompt the early detection of asymptomatic arteriopathy in individuals with NF1 in order to ameliorate patients' quality of life and life expectancy.